PERAN MEDIASI KEPUASAN KERJA PADA HUBUNGAN NILAI INDIVIDU DAN NILAI ORGANISASI DENGAN KOMITMEN ORGANISASIONAL DAN ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) KARYAWAN BALAI BESAR POM DI DENPASAR - rejeki, umiarti sri; Riana, I Gede; Priartini, Putu Saroyeni (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 ABSTRACT Quality of human resources could affect the achievement of vision, mission and organization goal through the suitability between individual value and organization value..? This research is aimed to know role of work satisfaction mediation toward relationship between congruency individual value and organization value with organizational commitmen and employee’s OCB in Regional Agency of Food and Drug Control of Denpasar. Population in this research are 96 responden  that work at in regional agency of food and drug control of Denpasar. Primary data was taken from respondent. Multiple regression analysis methode was used for hypothesis analysis as well ( Baron and Keynes, 1986) with SPSS version 17.0 was used as software application and then using a Sobel test to determined the effect if it’s significant. The result showed that (1) Congruency individual value  and organization value gave significant positive effect toward Organizational Commitment (2) Congruency individual value  and organization value gave significant positive effect toward OCB (3) Congruency individual value  and organization value gave significant positive effect toward work satisfaction (4) Work Satisfaction gave significant positive effect toward Organizational Commitment (5) Work satisfaction gave significant positive effect toward OCB (6) Work Satisfaction gave positive partially mediation but not signifikan toward relationship congruency individual and organization value with commitment organizational and employee’s OCB. Suggested for further research in order to broaden the scope of research into multiple organizational and separating respondendts into each position group, as well as examining in particular the role of intrinsic job satisfaction and extrinsic job satisfaction to see more job satisfaction factors affect the value of individual relationship and organizational values to organizational commitment and employee’s OCB in Regional Agency of Food and Drug Control of Denpasar. Keywords : Congruency Individual Value and Organizationa Value, Work Satisfaction, Organizational Commitment, Organizational Citizenship Behavior (OCB) .
Keywords: Congruency Individual Value and Organizationa Value, Work Satisfaction, Organizational Commitment, Organizational Citizenship Behavior (OCB).